EFEKTIVITAS PROJECT-BASED LEARNING DALAM MENINGKATKAN ENTREPRENEURIAL MINDSET MAHASISWA MPI - Rahayu Lestari; Shera Nabila Luvianingtias; Heru Juabdi Sada; Fisman Bedi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This study was motivated by the importance of strengthening students’ entrepreneurial mindset amid changes in the labor market that require graduates not only to be job-ready but also capable of creating independent business opportunities. However, learning practices in the Islamic Education Management (MPI) Study Program remain predominantly theoretical and have not optimally developed students’ entrepreneurial mindset. This study aims to analyze the effectiveness of Project-Based Learning (PjBL) in improving the entrepreneurial mindset of MPI students. The research employed a Systematic Literature Review (SLR) method using the PRISMA approach. Data were collected through scientific articles indexed in Google Scholar, Scopus, ScienceDirect, and DOAJ published between 2020 and 2025. The research stages included identification, screening, eligibility, and inclusion of articles based on predetermined criteria. Data were analyzed using content analysis techniques to identify themes, patterns, and key findings related to the implementation of PjBL and the development of entrepreneurial mindset. The findings indicate that PjBL effectively enhances creativity, problem-solving skills, risk-taking ability, self-efficacy, and students’ orientation toward creating business opportunities. PjBL also encourages active student engagement through contextual and collaborative learning experiences. Therefore, PjBL can serve as an effective learning strategy in developing the entrepreneurial mindset of MPI students in a holistic and sustainable manner. ABSTRAK Penelitian ini dilatarbelakangi oleh pentingnya penguatan entrepreneurial mindset mahasiswa di tengah perubahan dunia kerja yang menuntut lulusan tidak hanya siap kerja, tetapi juga mampu menciptakan peluang usaha secara mandiri. Namun, pembelajaran pada Program Studi Manajemen Pendidikan Islam (MPI) masih cenderung berorientasi teoritis dan belum optimal dalam mengembangkan pola pikir kewirausahaan mahasiswa. Penelitian ini bertujuan untuk menganalisis efektivitas Project-Based Learning (PjBL) dalam meningkatkan entrepreneurial mindset mahasiswa MPI. Metode yang digunakan adalah Systematic Literature Review (SLR) dengan pendekatan PRISMA. Data diperoleh melalui penelusuran artikel ilmiah dari Google Scholar, Scopus, ScienceDirect, dan DOAJ pada rentang tahun 2020–2025. Tahapan penelitian meliputi identifikasi, screening, eligibility, dan inclusion artikel sesuai kriteria penelitian. Data dianalisis menggunakan teknik content analysis untuk mengidentifikasi tema, pola, dan temuan utama terkait implementasi PjBL dan pengembangan entrepreneurial mindset. Hasil penelitian menunjukkan bahwa PjBL efektif meningkatkan kreativitas, kemampuan problem solving, keberanian mengambil risiko, self-efficacy, serta orientasi mahasiswa terhadap penciptaan peluang usaha. PjBL juga mendorong keterlibatan aktif mahasiswa melalui pengalaman belajar yang kontekstual dan kolaboratif. Dengan demikian, PjBL dapat menjadi strategi pembelajaran yang efektif dalam membentuk entrepreneurial mindset mahasiswa MPI secara holistik dan berkelanjutan.